2018
DOI: 10.1117/1.jbo.23.10.106501
|View full text |Cite
|
Sign up to set email alerts
|

Method to identify and minimize artifacts induced by fluorescent impurities in single-molecule localization microscopy

Abstract: . The existence of fluorescent impurities has been a long-standing obstacle in single-molecule imaging, which results in sample misidentification and higher localization uncertainty. Spectroscopic single-molecule localization microscopy can record the full fluorescent spectrum of every stochastic single-molecule emission event. This capability allows us to quantify the spatial and spectral characteristics of fluorescent impurities introduced by sample preparation steps, based on which we developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Autofluorescence is stronger at shorter wavelengths and can hence be alleviated using fluorophores with longer emission wavelengths and/or appropriate filters. Impurities can be reduced, although not entirely removed, by appropriate cleaning of coverslips, for example using plasma cleaners 206 .…”
Section: Sample Driftmentioning
confidence: 99%
“…Autofluorescence is stronger at shorter wavelengths and can hence be alleviated using fluorophores with longer emission wavelengths and/or appropriate filters. Impurities can be reduced, although not entirely removed, by appropriate cleaning of coverslips, for example using plasma cleaners 206 .…”
Section: Sample Driftmentioning
confidence: 99%
“…We developed sSMLM systems that utilize diffraction gratings to obtain the spatial and spectral information of the single-molecule blinking events simultaneously [16, 2124]. Using sSMLM, we reported that Rhodamine dyes tagged microtubules assembled in vitro showed significant spectral heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Future updates will make RainbowSTORM compatible with a wider range of spatial analysis platforms. Further, additional spectroscopic analysis methods such as spectral unmixing (Davis, et al, 2018), machine-learning based spectral classification (Zhang, et al, 2019), and cluster analysis (Bongiovanni, et al, 2016) will be added to RainbowSTORM.…”
Section: Discussionmentioning
confidence: 99%